Penerapan Pendidikan Budaya Organisasi untuk Meningkatkan Profesionalitas Kerja Karyawan - Imam Sugianto; Mas'ud Said; Pardiman Pardiman (IKIP PGRI Bojonegoro, 2023)
Abstract: Employee work professionalism is determined by the successful implementation of organizational culture education in an organization. The form of successful implementation of organizational culture education is reflected in the management of the organization which is determined through organizational principles and management changes made so that organizational goals can be achieved. Realistic implementation of organizational culture education will increase employee professionalism. This study aims to measure the increase in employee professionalism through the application of organizational culture education. The research method used is a descriptive qualitative approach with primary data sources. Data collection techniques through observation, interviews, and documentation. Processing and analysis of data in this study used several steps including data reduction, data presentation, drawing conclusions and verification. The results showed that in order to increase the work professionalism of employees at Khoiru Ummah Islamic Junior High School, it is necessary to apply organizational culture education through instilling organizational change values and action in developing organizational culture. Planting organizational change values through increasing employee integrity, competence, and creativity, fostering an accountable attitude, and fostering concern among employees. Organizational culture development action is carried out through the implementation of communication, programs to improve the quality of human resources, and dispositions. The output resulting from the application of organizational culture education to increase employee work professionalism is in the form of work quality, punctuality, effectiveness, and loyalty. Abstrak: Profesionalisme kerja pegawai ditentukan oleh keberhasilan penerapan pendidikan budaya organisasi pada suatu organisasi. Bentuk keberhasilan penerapan pendidikan budaya organisasi tercermin dari pengelolaan organisasi yang ditentukan melalui prinsip organisasi dan perubahan manajemen yang dilakukan agar tujuan organisasi dapat tercapai. Penerapan pendidikan budaya organisasi secara realistis akan meningkatkan profesionalisme kerja pegawai. Penelitian ini bertujuan untuk mengukur peningkatan profesionalisme pegawai melalui penerapan pendidikan budaya organisasi. Metode penelitian yang digunakan yakni pendekatan kualitatif deskriptif dengan sumber data primer. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Pengolahan dan analisis data dalam penelitian ini menggunakan beberapa langkah antara lain reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan untuk meningkatkan profesionalisme kerja pegawai di SMP Islam Khoiru Ummah diperlukan penerapan pendidikan budaya organisasi melalui penanaman nilai organizational change dan action dalam mengembangkan budaya organisasi. Penanaman nilai organizational change melalui peningkatan integritas, kompetensi, dan kreativitas pegawai, menumbuhkan sikap akuntabel, serta memupuk kepedulian antar pegawai. Action pengembangan budaya organisasi dilakukan melalui implementasi komunikasi, program peningkatan kualitas sumber daya, dan disposisi. Output yang dihasilkan dari penerapan pendidikan budaya organisasi untuk meningkatkan profesionalisme kerja pegawai berupa kualitas kerja, ketepatan waktu, efektifitas, dan loyalitas.